Aspects of a Theory and the Present State of Speech Synthesis - Boras, Damir (Array, 2006)
The intent of this paper is to present the research and the results obtained on speech synthesis in the Departments of Phonetics and Information Sciences, University of Zagreb, Croatia. The state of the speech synthesis technology in the world and its methods are reviewed. The topics dealt with are: converting written language into sounds, length of sounds and words, sentence and word intonation.Difficulties and problems arising in different languages are analysed. Various synthesis techniques are discussed.